Analytical, Experimental and Numerical Analysis of Pure Bending of Aluminum Beams with Artificially Produced Structure (Proceedings of Faculty of Civil Engineering, 2021)
This paper considers strains in pure bending of homogeneous and heterogeneous beams. The strains are determined analytically, experimentally, by the strain-gauge method, and numerically, by using the finite element method. The geometry of the specimens that gives the beams heterogeneous structure has been defined and the expression for the second moment of area derived. The aim of this paper is to test the applicability of the beam theory to the analysis of heterogeneous isotropic and orthotropic structures. The results of the three approaches are compared using the experimental results as a reference set of data.
Keywords: Pure bending; second moment of area; beam theory; strain-gauge measurement; heterogeneous beams